ANALISIS SUMBER-SUMBER PENDAPATAN ASLI DAERAH SETELAH SATU DEKADEOTONOMI DAERAH - Nasir, Muhammad Safar (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2019)
Implementation of regional autonomy that is already more than a decade of implementatiaon of development pursued by local government through funding of local revenue (PAD). The purpose of this study analysis the contribution, knowing the potential growth rate, elasticity, as well as the estimated brag-source revenue in the future. This study uses secondary data from fiscal year 2007-2013 for the entire District Municipality in Indonesia with an analysis of the description. This research technique using the technique of contribution ratio, growth ratio, the ratio of elasticity and ratio trend analysis. These results indicate that the contribution and elasticity of PAD sources found that local taxes, and other legitimate PAD is the largest contributor to PAD in the District of Indonesian City while the levy and enterprises still contribute and elasticity is small, While the growth rate of PAD sources would have a growth rate trend fluctuatif.